Controlling the emission in flexibly-linked (N^C^N)platinum dyads. Issue 1 (4th December 2017) - Garoni, Eleonora; Boixel, Julien; Dorcet, Vincent; Roisnel, Thierry; Roberto, Dominique; Jacquemin, Denis; Guerchais, Véronique
Abstract : Comparative luminescence studies of the mononuclear complexPt-1 and the differently linked dinuclear complexesPt-2 andPt-3 reveal distinctive luminescent properties. The emission ofPt-2 can be readily modulated over a wide range of the visible part of the spectrum. Abstract : The synthesis, spectroscopic and theoretical characterizations of dinuclear Pt(ii ) complexes where the two chromophoric units are connected though a polyether chain via either the central benzene ring of the tridentate ligand dpyb (Pt-2 ), or the phenylacetylide ligand (Pt-3 ), are described. The spacer, which contains four oxyethylene –CH2 CH2 O– units, is flexible and long enough to allow a self-association of the Pt units by folding, as shown by DFT calculations. Comparison of the photophysical properties of the dinuclear complexPt-2 with those of the mononuclear complexPt-1, used as reference, demonstrates the key role played by the linker group in the interaction processes. In addition, the emission of complexPt-2 was found to be affected by the temperature, nature of the solvent, and cation coordination as evidenced by luminescence and 1 H NMR studies. The interacting processes are highly dependent on the solvent polarity that controls the – extended vs folded – arrangement and, consequently, induces solvatochromic shifts. This unique photophysical behavior ofPt-2 allows the modulation of the emission from green to deep-red (up to 125 nm) over the visible part of the spectrum. By contrast, complexPt-3 has a high propensity to form a red-shifted intense emissive excimer. DFT and TD-DFT investigations of the excimers inPt-2 andPt-3 consistently show a much stronger interaction in the latter complex.